Student emotions in class: The relative importance of teachers and their interpersonal relations with students. (February 2018) - Mainhard, Tim; Oudman, Sophie; Hornstra, Lisette; Bosker, Roel J.; Goetz, Thomas
Abstract: This study highlights the importance of teachers in relation to the emotions students experience in class. First, in line with the work of Kenny, we argue that the specific relationship that evolves between teachers and students drives students' emotional experiences. We decompose variability in student emotions not only into the commonly investigated student and teacher facets but also into facets representing specific pairings of teachers with classes and students (so-called relationship effects). Second, using interpersonal theory, we assess the degree to which the interpersonal quality of teaching accounts for variability in student emotions. Cross-classified multilevel modelling of 8042 student ratings (N = 1668 secondary school students, M age = 14.94) of 91 teachers indicated that a considerable amount of variability that is usually assigned to the student level may be due to relationship effects involving teachers. Furthermore, the way that teachers interpersonally relate to their students is highly predictive of student emotions. In sum, teachers may be even more important for student emotions than previous research has indicated. Highlights: Previous studies have probably overestimated emotional variability at the student level. The way that teachers adjust with specific students and classes affects student emotions. Teacher agency (power) and communion (warmth) predict student emotions. Teachers may play a more prominent role in student emotions than has been assumed to date. Research on classroom environmental effects can benefit from cross-classified models.